Information processing method and apparatus for encrypting encoded data - Hayashi, Junichi (2008)
The present invention makes it possible to encrypt a portion of a tile image to be subject to wavelet transformation at or above a desired resolution level without the need to manage multiple encryption keys. The invention divides the sub-bands generated with each wavelet transformation into a plurality of precincts, treats aggregations of encrypted data of precincts of the same phase of sub-bands of the same layer as a tile part, and defines a tree structure in which tile parts having higher frequency encrypted data are positioned at higher level nodes. An encryption unit then generates encryption key information for tile parts of the highest level node based on route key information generated from encrypted data for the entire tile, and generates encryption key information for encrypting tile parts other than those of the highest node by unidirectional transformation of encryption key information for tile parts of higher level nodes.